Mixed spinel and perovskite phased LaSrNiO nanoparticles as cathode catalyst for non-aqueous lithium-oxygen batteries. (10th September 2019) - Li, Xingyu; Zhu, Tianjiao; Wen, Caiying; Yang, Yan; Ma, Shulan; Huang, Xianqiang; Li, Huifeng; Sun, Genban
Abstract: LaSrNiO nanoparticles with different doping amount of strontium are synthesized through sol-gel method accompanied by high-temperature calcination. With the increase of Sr content, the crystal structure of samples changes from perovskite to spinel phase that promote both oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) property. As a cathode catalyst for Li-O2 battery, LaSrNiO nanoparticles show a capacity performance of 9000 mAh·g −1 and significantly enhanced cyclability. The improved battery performance with Sr-doped nanoparticles can be ascribed to the high surface area of Sr-doped LaSrNiO nanoparticles combined with mixed spinel and perovskite phased structure which facilitate specific capacity and OER performance obviously. This research work is believed to shed light on a new thought to boost the performance of Li-O2 battery. Highlights: LaSrNiO are prepared via sol-gel way accompanied by high-temperature calcination. LaSrNiO nanoparticles possess mixed perovskite and spinel phase for Sr doping. Unique crystal structure of LaSrNiO effectively boost Li-O2 battery performance.